Alternative Economies of the Forest: Honey Production and Public Land Management in Northwest Florida. Issue 3 (4th March 2017) - Watson, Kelly
ABSTRACT: Within public lands across the United States, "natural" environments are given boundaries, subject to regulation, and managed for various uses. However, the effective and judicious management of these socionatural spaces for the greater good of both long-term sustainability and the mutual benefit of disparate stakeholders remains a challenge. One such stakeholder group includes forest-dependent communities, specifically, harvesters and producers of nontimber forest products (NTFPs). Relying on a case study of honey producers in rural northwest Florida, this article demonstrates how competing notions of forest management create tensions between local resource users and resource managers. NTFP research engages in timely discussions of diverse economic practices, resource politics, and issues of contested land use and access within a post-industrial context.